Organophosphate Poisoning and Subsequent Acute Kidney Injury Risk: A Nationwide Population-Based Cohort Study. Issue 47 (November 2015) - Lee, Feng-You; Chen, Wei-Kung; Lin, Cheng-Li; Lai, Ching-Yuan; Wu, Yung-Shun; Lin, I-Ching; Kao, Chia-Hung
Abstract : Abstract: Small numbers of the papers have studied the association between organophosphate (OP) poisoning and the subsequent acute kidney injury (AKI). Therefore, we used the National Health Insurance Research Database (NHIRD) to study whether patients with OP poisoning are associated with a higher risk to have subsequent AKI. The retrospective cohort study comprised patients aged ≥20 years with OP poisoning and hospitalized diagnosis during 2000–2011 (N = 8924). Each OP poisoning patient was frequency-matched to 4 control patients based on age, sex, index year, and comorbidities of diabetes, hypertension, hyperlipidemia, chronic obstructive pulmonary disease, coronary artery disease, and stroke (N = 35, 696). We conducted Cox proportional hazard regression analysis to estimate the effects of OP poisoning on AKI risk. The overall incidence of AKI was higher in the patients with OP poisoning than in the controls (4.85 vs 3.47/1000 person-years). After adjustment for age, sex, comorbidity, and interaction terms, patients with OP poisoning were associated with a 6.17-fold higher risk of AKI compared with the comparison cohort. Patients with highly severe OP poisoning were associated with a substantially increased risk of AKI. The study found OP poisoning is associated with increased risk of subsequent AKI. Future studies are encouraged to evaluate whether long-term effects exist and the best guideline to prevent the continuously impaired renal function.